Ultra‐Long Crystalline Red Phosphorus Nanowires from Amorphous Red Phosphorus Thin Films. Issue 39 (24th August 2016) - Smith, Joshua B.; Hagaman, Daniel; DiGuiseppi, David; Schweitzer‐Stenner, Reinhard; Ji, Hai‐Feng
Abstract: Heating red phosphorus in sealed ampoules in the presence of a Sn/SnI4 catalyst mixture has provided bulk black phosphorus at much lower pressures than those required for allotropic conversion by anvil cells. Herein we report the growth of ultra‐long 1D red phosphorus nanowires (>1 mm) selectively onto a wafer substrate from red phosphorus powder and a thin film of red phosphorus in the present of a Sn/SnI4 catalyst. Raman spectra and X‐ray diffraction characterization suggested the formation of crystalline red phosphorus nanowires. FET devices constructed with the red phosphorus nanowires displayed a typical I –V curve similar to that of black phosphorus and a similar mobility reaching 300 cm 2  V −1  s with an I on / I off ratio approaching 10 2 . A significant response to infrared light was observed from the FET device. Abstract : Red, red wire : The heating of amorphous red phosphorus powder and a thin film of red phosphorus film on a silicon wafer in a sealed ampoule resulted in a mm‐long, uniform, and dense phosphorus nanowire network. Field effect transistor (FET) devices constructed with the red phosphorus nanowires displayed similar properties black phosphorus. A significant response to infrared light was observed from the FET device.